Identificación de acciones de salud en el Programa de Control de Sífilis en gestantes, Cartagena de Indias, 2016. - Cárdenas Dávila, Elvisa; Bedoya Marrugo, Elías Alberto; Arnold Domínguez, Yuri; Manrique-Julio, Elin (NOVA: Publicación Científica en Ciencias Biomédicas)
Basis. Congenital Syphilis is an infection caused by the hematogenous spread of Treponema pallidum from the pregnant woman infected to the fetus. At the time of pregnancy, control of the disease during pregnancy is vital in prenatal care. Objective. To identify the fulfillment of the health actions included in the Syphilis Control Program in pregnant women of the city of Cartagena de Indias, first half of 2016. Materials and methods. Cross-sectional descriptive observational study. A total of 781 prenatal control pregnant women were evaluated in the city, through the institutions that provide health services (PHI) and health promotion companies (PHE). Results. Gestation was completed in 358 (45.8%) of the pregnant women studied. In 25 (6.5%) of the total, intrapartum VDRL was not performed. During the first trimester of pregnancy 99.6% of the resulting nonreactive VDRL (NR) evaluations. While in the second trimester, they were evaluated, 67.5% and 57.4%, respectively; resulting reactive VDRL (R) one (0.1%) during both semesters trimesters. From the second to the third trimester of pregnancy, the number of pregnant women was not increased (98, 12.5%) and (63, 8, 1%), however, if it increased (55, 19.8%) (269; 34.4%), respectively, pregnant women who are waiting for the time to perform the test. There is no co-infection Syphilis/HIV/AIDS. Conclusions. The control of syphilis during prenatal care was deficient given the high rate of non-adherence in the compliance of the treatment in the pregnant woman, as their tests were not made according to the time established by the health team.